Taisir al-Nahw al-‘Arabi: Analisis Pemikiran Mahdi al-Makhzumi dalam Pembaruan Nahwu - Holilulloh, Andi; Sugiyono, Sugeng; Afandi, Zamzam (Institut Agama Islam Negeri Curup, 2021)
The study of classical nahwu is considered too difficult and also makes it more difficult for the learners to learn. The critics to classical nahwu began to come from the Middle Ages to modern because it was considered to be full of Greek philosophy and logic so that Al-Makhzumi attempted to reform the nahwu. This article aims to further examine Al-Makhzumi's thoughts in his theory of Taisir al-Nahwi al-‘Arabi and the update of Nahwu. This research uses a qualitative method applied in library research. The results of this study indicate that Al-Makhzumi saw a language through a descriptive method until he created the theory of taisir an-nahwi al-‘Arabi with the aim of making the study of nahwu easier and more suitable to the context of learners’ needs today. According to Al-Makhzumi, there are eight basic principles used in the taisir an-nahwi al-‘Arabi theory, they are: (1) refusing the theory of ‘amil, (2) systematic rearrangement of chapters and topics of nahwu study, (3) consolidating Arabic phonology and Arabic morphology in Arabic syntax, (4) supporting speaking proficiency is the basis of Ibn Madha's nahwu critique method, (5) redefining some of Arabic syntax chapters, (6) removing branches and unnecessary chapters of nahwu such as removing i'rab mahalli and taqdiri, (7) perfecting the chapters deemed necessary to be perfected, and (8) consolidating ma’ani aspects in the arabic syntax written on asalib at-ta’bir. This theory is produced by Al-Makhzumi from several sources, including: Imam Khalil ibn Ahmad al-Farahidi, school of Kufah (Imam al-Farra’), Ibn Madha', and Ibrahim Mushtafa.